2019
DOI: 10.1136/bmjopen-2019-031811
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of the endometrium and timing of blastocyst transfer in modified natural cycle frozen-thawed embryo transfers (mNC-FET): a study protocol for a randomised controlled multicentre trial

Abstract: IntroductionDespite the high number of frozen embryo transfer (FET) cycles being conducted (190 000 cycles/year) in Europe, the timing of blastocyst transfer and the use of luteal phase progesterone support in modified natural cycle FET (mNC-FET) in assisted reproductive technologies are controversial. In mNC-FET, the timing of blastocyst warming and transfer is determined according to the time of implantation in a natural cycle, aiming to reach blastocyst endometrial synchronicity. However, the optimal day of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…They concluded that single LH determination prior to ovulation induction in unstimulated cycle FET does not seem to have added clinical value [ 17 ]. However, Saupstad et al [ 20 ] reported that in a natural cycle the follicle size corresponding to the start of LH rise varies between different patients. Therefore, relying on follicular size only may result in the administration of hCG either too early or too late, consequently adversely affecting endometrial receptivity, thereby resulting in asynchronicity between the endometrium and the transferred blastocyst.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that single LH determination prior to ovulation induction in unstimulated cycle FET does not seem to have added clinical value [ 17 ]. However, Saupstad et al [ 20 ] reported that in a natural cycle the follicle size corresponding to the start of LH rise varies between different patients. Therefore, relying on follicular size only may result in the administration of hCG either too early or too late, consequently adversely affecting endometrial receptivity, thereby resulting in asynchronicity between the endometrium and the transferred blastocyst.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that FET has increased risks in terms of gestational age babies and hypertensive disorders of pregnancy [ 14 18 , 40 ]. However, the specific mechanism of these pregnancy complications after FET remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Patients are often concerned about whether FET or OC poses a risk to offspring perinatally or after birth. Regarding FET, there are consistent findings of an increased risk of hypertensive disorders of pregnancy and large for gestational age after FET, but the specific reasons for this are not clear [ 14 18 ]. Some studies have suggested that the risks might be relevant to FET, as FET may lead to epigenetic changes [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a Scandinavian multi-center RCT is currently ongoing to explore the optimum timing for transferring a single frozen-warmed blastocyst in modified-NC, that is, hCG+6 days or hCG+7 days (78). In this study, each group is further assigned to receive LPS or not.…”
Section: Timing Of Embryo Transfer In T-nc and Modified-ncmentioning
confidence: 99%